BIGSAS Festival of African and African-Diasporic Literatures | July 5-7, 2019 (BIGSAS Literature Festival 2019, 2020)
The BIGSAS Festival of African and African-diasporic Literatures, as an annual tradition, runs for three consecutive days as an entrance free event in the heart of Bayreuth, hosting writers, scholars and activists. Throughout this event, negotiations of wor(l)d making within arts, academia and activism are addressed, while re/visiting the un/making of collective knowledges and respective practices. Readings, performances, lectures, panel discussions, workshops and (street) music are composed to invite an interested audience from all over Bayreuth and beyond to become an intergenerational, transcultural, transregional, multidimensional community where strategies of inclusivism are practiced in a setting fraught with “unity in diversity” (Glissant). The festival opened with a demonstration FridaysForFuture+ on campus of the University of Bayreuth continued to the refugee house at Wilhelm-Buschstraße to arrive in the city center with a manifest through perfromances by BLESZ and Musa Okowonga. Successivly, the festival opened its 9th edition officially at the IWALEWAHAUS to enable a public access to topic centered around anti-racist and feminist discourses of crises and responsibility also in the context of environmental awareness. These issues were expressed in keynotes, readings, music and spoken word performances, an art exhibition and round table discussions. These events were all free of entry to the public domain. The festival is hosted by the Bayreuth International Graduate School of African Studies (BIGSAS) which is part of the Africa Multiple Cluster of Excellence (funded by DFG). https://2019.bigsas-litfestival.com/ - Follow us on Social Media: Facebook - https://www.facebook.com/pg/AfricaMultiple Instagram - https://www.instagram.com/exc2052/ Twitter - https://twitter.com/ClusterAfrica https://www.africamultiple.uni-bayreuth.de/